(untitled) (Fiep Bulletin - online, 2013)
This study aimed at characterizing the kinematics locomotion held in suspension in the liquid medium. This case study was to sample a man of 45 years. The angles of the joints were examined knee, hip, elbow, shoulder (for angles) and inclination of the trunk. The angular variations were measured during 03 cycles of locomotion, by shooting two-dimensional. Data analysis was used Pearson’s linear correlation (p <0.01). It can be observed correlations presented by that, with regard to the synchrony of movement, the movement performed during locomotion matter was similar to that motion on land, by synchronous movements of nearly all body parts, because, for range of motion joint researched, this data comes from meeting the figures given by the literature when referring to the model’s gait on land. Still, you can see differences between support made while walking on land and those found in this study.